1996
DOI: 10.1523/jneurosci.16-15-04707.1996
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ERK ( Extracellular Signal Regulated Kinase), Part of the Neurotrophin Signal Transduction Cascade, in the Rat Mesolimbic Dopamine System by Chronic Exposure to Morphine or Cocaine

Abstract: Local infusion of brain-derived neurotrophic factor (BDNF) into the ventral tegmental area (VTA) can prevent and reverse the ability of chronic morphine or cocaine exposure to induce tyrosine hydroxylase (TH) in this brain region. The present study examined a possible role for extracellular signal regulated kinases (ERKs), the major effector for BDNF and related neurotrophins, in morphine and cocaine action in the VTA. Chronic, but not acute, administration of morphine or cocaine increased ERK catalytic activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
231
4
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(257 citation statements)
references
References 43 publications
18
231
4
1
Order By: Relevance
“…Animal data suggest that ERK might be involved in regulation by opiate drugs of tyrosine hydroxylase, with protein levels increased in rat "striatum" (the rodent counterpart of the human caudate and putamen) following chronic morphine administration (Ortiz et al 1995;Berhow et al 1996). Our data suggest, however, that any regulation by ERK of tyrosine hydroxylase in the human does not involve changes in actual striatal levels of ERK.…”
Section: Erkmentioning
confidence: 61%
See 1 more Smart Citation
“…Animal data suggest that ERK might be involved in regulation by opiate drugs of tyrosine hydroxylase, with protein levels increased in rat "striatum" (the rodent counterpart of the human caudate and putamen) following chronic morphine administration (Ortiz et al 1995;Berhow et al 1996). Our data suggest, however, that any regulation by ERK of tyrosine hydroxylase in the human does not involve changes in actual striatal levels of ERK.…”
Section: Erkmentioning
confidence: 61%
“…Wakabayashi et al 1995, we measured levels of dopamine metabolites (homovanillic acid, 3-methoxytyramine, dihdroxyphenylacetic acid), serotonin and metabolite 5-hydroxyindoleacetic acid, and noradrenaline. Finally, as experimental animal data show that chronic opiate administration can upregulate striatal concentrations of extracellular signal-regulated kinases (ERKs), signaling molecules that may be involved in the regulation of levels of tyrosine hydroxylase (Ortiz et al 1995;Berhow et al 1996), we also determined striatal concentration of ERK2 in the heroin users. Our biochemical findings suggest that chronic heroin exposure might modestly decrease both dopaminergic and serotonergic function in the human.…”
Section: To Establish Whether Chronic Opiate Exposure Might Impair Brmentioning
confidence: 99%
“…No changes in total ERK and CREB were observed at any dose and no changes in P-ERK or P-CREB were observed in animals of either genotype treated with 0.25 mg/kg morphine (not shown). Since inhibition of ERK1/2 phosphorylation in the VTA blocks the rewarding effects of morphine (Berhow et al, 1996;Ozaki et al, 2004), the observed increases in ERK1/2 activation may regulate (a) Galanin wild-type (WT; n ¼ 10) and knockout (GKO; n ¼ 11) mice were administered an acute i.p. injection of saline followed by 0, 5, 10, or 20 mg/kg morphine 15 min later.…”
Section: Neurochemical Changes Downstream Of Morphine Signalingmentioning
confidence: 99%
“…These studies further examined whether second messenger signaling pathways that support these morphine-regulated behaviors are modulated by galanin. At the molecular level, morphine administration leads to enhanced phosphorylation, and thus activation of extracellularregulated kinase (ERK1/2) in the VTA, hippocampus, NAc, cingulate cortex, and amygdala (Berhow et al, 1996;Valjent et al, 2004). Increased ERK1/2 phosphorylation in the VTA is associated with morphine and psychostimulant reward (Ozaki et al, 2004) and systemic inhibition of ERK1/2 phosphorylation blocks expression of morphine and cocaine CPP (Valjent et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…This concept was supported by a previous report using rats that received an infusion of BDNF into the ventral tegmental area, preventing drug-induced adaptations in a brain region known to be involved in drug reinforcing behavior. 20 The essential functional role of BDNF in TrkB-mediated signaling was demonstrated in a model of neurodegeneration, where survival of hippocampal neurons in culture derived from trisomy 16 mice, which produce the truncated kinasedeficient isoform, Trk-T1, and would be destined to die were restored by introduction of exogenous full-length TrkB. 21 A role for TrkB linked to AD in humans has not been reported.…”
Section: Introductionmentioning
confidence: 99%